Analisis Kebutuhan Guru Bahasa Arab MTS Dan MA Di Kota Kotamobagu - Stion, Lystira Nurfitrianisa; Hairuddin, Hairuddin; I. Miolo, Mukhtar (Assuthur: Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to provide an overview of how the distribution map of Arabic teachers at the MTs and MA levels in Kotamobagu City in 2023 is presented in the form of a table and described descriptively. This research is a type of descriptive quantitative research, with data collection techniques using questionnaires, interviews and documentation. The results of this study show that there are 16 Arabic teachers spread across 4 MTs and 2 MA in Kotamobagu City. Based on this number, there are still teachers who have non-Arabic education backgrounds. From this number, it is also known that most of these teachers have not been certified educators according to the subjects they are taught. The shortage and excess of teaching hours is also a phenomenon that also occurs in Arabic teachers in Kotamobagu City. So based on the results of the analysis and calculations that have been carried out, it is known that the distribution of Arabic teachers at both the MTs and MA levels in Kotamobagu City is not evenly distributed.